2017
DOI: 10.1590/1678-4162-9259
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical composition of the hoof capsule of buffaloes and its influence on hoof quality

Abstract: The purpose of this study was to establish the biochemical parameters of the abaxial wall, dorsal wall and sole of the hoof of the medial thoracic, lateral, and medial pelvic digits of buffalos. The hoof samples were subjected to destructive biochemical analyses to identify the dry material (DM), mineral matter (MM), organic matter (OM), crude protein (CP) and ether extract (EE) contents. Sulfur (S), calcium (Ca), potassium (K), phosphorus (P), zinc (Zn) and copper (Cu) levels were determined based on nondestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…EDXRF proved to be an effective technique for the quantification of minerals in the superficial layers of the hoof wall, corroborating the results of Assis, Vulcani, et al. (2017). We observed that daily supplementation with 20 mg of biotin increased the concentration of sulphur (S) and reduced the concentration of calcium (Ca) and potassium (K) (Tables 2 and 3).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…EDXRF proved to be an effective technique for the quantification of minerals in the superficial layers of the hoof wall, corroborating the results of Assis, Vulcani, et al. (2017). We observed that daily supplementation with 20 mg of biotin increased the concentration of sulphur (S) and reduced the concentration of calcium (Ca) and potassium (K) (Tables 2 and 3).…”
Section: Discussionsupporting
confidence: 86%
“…The hoof samples were cleaned and the attached soft tissue removed (Figure 1b) before being stored in plastic bags, identified and frozen at −22°C (Assis, Vulcani, et al., 2017). The samples were transported in a styrofoam box with ice.…”
Section: Methodsmentioning
confidence: 99%
“…The methods used affected all the minerals analysed for, as the ash content in proximate composition was low which resulted in low mineralisation this supports the findings of (Owen et al, 1953a;1953b) higher mineralization of hoof in soil due to heat treatment. There were however variations in the minerals of this study to that of (Gohl, 1981;AFRIS, 2012;Assis et al, 2017).…”
Section: Mineral Compositionmentioning
confidence: 50%
“…These were carried out in order to break the disulphide bond which makes keratin product protein unavailable for usage by livestock. The crude protein were higher than that reported for mixture of horn and hoof meal 88.6 % (Gohl, 1981); feather meal 81.15 % (Falaye, 1982); 83.02 % (Omitoyin, 1995); and lower than that of (AFRIS, 2012) 93.3 % for Cattle horn and hoof and (Assis et al, 2017) 91.67 % for buffalo hoof but within the range reported for raw hoof 92.38 % by (Owen et al, 1953a). The fat content was lower than that reported by (Falaye, 1982) 6.7 %; (Omitoyin, 1995) 1.84 %; (AFRIS, 2012) 4.7 %; (Adejumo et al, 2016) 5.19 %; while ash in raw hoof was similar to that of raw feather 2.34 % (Omitoyin, 1995) but lower to (Adejumo et al, 2016).…”
Section: Proximate Compositionmentioning
confidence: 56%
“…The main limitation of water buffaloes is that they are slower at work [ 18 ]. Nevertheless, they possess unique attributes, such as strength and tough hooves, and resistance to disease [ 19 ] that gives important advantages for working in wetlands and flooded, heavy, clay soils, where the efficiency of agricultural machinery tends to be limited [ 20 ]. Their life cycle as draught animals can last for as much as two decades [ 4 , 20 ].…”
Section: Current Usementioning
confidence: 99%